(untitled) (Scientific journal of the Fergana State University, 2026)
This research is devoted to the psycholinguistic study of speech ontogenesis within linguistics, focusing on the formation of speech ability, its developmental stages, and age-related changes in an individual’s language. The main aim of the study is to reveal the psychological and linguistic mechanisms underlying individual speech development and to identify general patterns of language acquisition in children. The methodological framework is based on comparative-analytical analysis, observation, and experimental methods. The empirical material includes child speech diaries, linguistic and psychological test results, as well as the works of leading Russian and Western scholars. The findings demonstrate that speech ontogenesis is interconnected not only with the linguistic system but also with cognitive development, communicative needs, and social factors. Moreover, it was established that the morphological, syntactic, and lexical stages of child speech development follow specific psycholinguistic regularities. In conclusion, the psycholinguistic study of speech ontogenesis provides a solid scientific and practical basis for improving methodological approaches to child speech formation, developing effective language teaching strategies, and fostering children’s cognitive and communicative competencies.